Jurnal Sri Mulyono PELAYANAN KANTOR KELURAHAN SEWU KECAMATAN JEBRES KOTA SURAKARTA, PROVINSI JAWA TENGAH: Jurnal Sri Mulyono - Sri Mulyono (JI@P, 2022)
Public services at the kelurahan level are interesting to observe because theiractivities are in the context of meeting the basic needs of the community for goodsor services and administrative services related to the interests of the community.The purpose of the study was to describe and analyze the services of the SewuVillage Office, Jebres District, Surakarta City. The research method usesdescriptive qualitative. Informants are employees of Sewu Village and residents ofSewu Village. Data collection techniques using interviews, observation, anddocumentation. The data analysis technique uses an interactive analysis model.The data validity technique uses source triangulation.Based on the results of the research and discussion, it can be concluded that:Services at the Sewu Village Office related to Tangibles (direct evidence),Reliability (reliability), Responsiveness (responsiveness), Assurance (guarantee),and Empathy (empathy) have been implemented well enough by employees so thatthere is social interaction between kelurahan employees and service users. Theresults of this study indicate that the service in Sewu Village has been runningwell although it has not been maximized due to several obstacles due toinadequate facilities and infrastructure, technical constraints and existing humanresources, but all of them can still be overcome so that services can run asplanned.Keywords: tangible, reliability, responsiveness, assurance, and empathy.